follow me : Britische Kunst an der Unterelbe. - Berq, Stephan; Bohlmann, Dieter-Theodor; Curtis, Penelope; Dennberg, Hans-Eckhard; Fiedler, Beate-Christine; Frerichs, Klaus; Gormley, Antony; Hall, James; Kwastek, Heidi; Marlow, Tim; Mawick, Rainer; Mayerhofer, Susanne; et al. (Stade : Landschaftsverband Stade, 1997)
Gormley, Antony ; Charlton, Alan ; Quinn, Marc ; Kapoor, Anish ; Houshiary, Shirazeh ; Opie, Julian ; Craig-Martin, Michael ; Wilson, Jane & Louise ; Landy, Michael ; Patterson, Simon ; Gordon, Douglas ; Wearing, Gillian ; Opie, Julian ; Armitage, Kenneth ; Brown, Ralph ; Butler, Reg ; Dalwood, Hubert ; Davis, John Warren ; Hoskin, John ; McWilliam, F.E. ; Meadows, Bernard ; Moore, Henry ; Paolozzi, Eduardo ; Thornton, Leslie Tillotson ; Wright, Austin
bibliografie
biografie
Follow Me : Britische Kunst an der Unterelbe / British Art on the Lower Elbe, 6. September - 31. Oktober 1997
boek
Keywords: Groot-Brittannië